DIGITAL TECHNOLOGIES AND THEIR ROLE IN ENSURING ENVIRONMENTAL SAFETY (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article discusses the importance of digital technologies in all sectors of our society, including their role in ensuring environmental safety. Additionally, the reforms being implemented in our country to ensure environmental safety are also discussed.